New catalytic strategy through confined explosions - Ponce Narvaez, Paula Dayana (2024)
The development of a new method of catalysis by confined explosions was successfully achieved by modifying a metal-organic framework (MOF) with a copper metal center called HKUST-1 (CuBTC) modified with different amounts of TNT doping. Various characterization techniques and computational strategies were employed to confirm the accurate synthesis of TNT, distinguishing it from its precursor DNT. XRD analysis revealed crucial insights into the crystal packing phases in TNT. For the MOF analysis, computational simulations were performed for three different structural models to analyze the position of TNT inside HKUST-1. Both experimental and theoretical approaches for different characterization techniques confirmed the presence of TNT in the MOF. XRD analysis further validated the correct synthesis of HKUST-1, with variations in peaks corresponding to different TNT doping levels. XPS studies highlighted significant differences in both structures, particularly in the Cu environment and the peaks of O1s and C1s, confirming the successful coordination of TNT within the MOF. In catalytic applications, TATP, a primary explosive, was synthesized and characterized, then was used to ignite the TNT explosión inside HKUST-1. Catalytic testing demonstrated HKUST-1-TNT’s efficacy, as evidenced by UV-visible studies tracking rapid reaction kinetics and the formation of small sulfur rings, in contrast of the typical kinetic reaction that commonly yields larger sulfur rings. In this way, the synthesis and characterization of a HKUST-1 doped with TNT was achieved and tested as a promising new catalyst that could generate a new branch of catalysis with an infinite number of materials and reactions that could be explored.